Literary Intransigence: Between J. Hillis Miller and Ranjan Ghosh. Issue 3 (December 2017) - Van Den Abbeele, Georges
Abstract : Hillis Miller and Ranjan Ghosh think literature from opposite but complementary points of view. Miller is the advocate of close reading and generally an inductive approach whereby specific interpretive problems in regard to specific literary texts critically revise broader theoretical assumptions and presuppositions. Ghosh, on the other hand, plays the consummate theorist, appropriating and critically developing various concepts in dialogue with a wide range of contemporary critical voices, then applying that revised/expanded concept to the analysis of specific works. Each models a different way to move between theory and interpretation, but both ground their thinking in the strangeness of literature, what Miller calls its 'idiosyncrasy' and Ghosh, based on his reinvigoration of the Hindi term, sahitya, its sacredness. This piece argues for the fundamental 'foreignness' of literature (and culture in general) as underwriting both approaches. Following upon Voloshinov, Benjamin, and others, I situate both theory and criticism of literature within the larger problem of translation as a crossing between languages that also brings the foreign into the native tongue, an irreducibility I call literary intransigence. As opposed to platitudes about 'world' literature, literary intransigence implies instead a vigorous reading of all literature as foreign.